2014
DOI: 10.3899/jrheum.130949
|View full text |Cite
|
Sign up to set email alerts
|

Is the Madrid Sonographic Enthesitis Index Useful for Differentiating Psoriatic Arthritis from Psoriasis Alone and Healthy Controls?

Abstract: The severity of US entheseal abnormalities is highest in patients with PsA followed by PsC and is lowest in healthy controls. MASEI can specifically classify patients as having PsA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 20 publications
1
44
0
6
Order By: Relevance
“…Clinical characteristics included self‐reported pain at the enthesis (on either the PEST questionnaire or the EARP questionnaire or in the history) or the presence of a tender enthesis at clinical examination (LEI/MASES). We did not accept the sole presence of power Doppler signal, as study data suggest that power Doppler signal could be present in nonclinical cases .…”
Section: Methodsmentioning
confidence: 93%
“…Clinical characteristics included self‐reported pain at the enthesis (on either the PEST questionnaire or the EARP questionnaire or in the history) or the presence of a tender enthesis at clinical examination (LEI/MASES). We did not accept the sole presence of power Doppler signal, as study data suggest that power Doppler signal could be present in nonclinical cases .…”
Section: Methodsmentioning
confidence: 93%
“…Reading of the US scans was performed independently from the clinical data by a single reader (LE). The intraobserver intraclass correlation coefficient for the MASEI was 0.8 (25). HLA genotyping.…”
Section: Methodsmentioning
confidence: 94%
“…PsA and healthy controls (85), and magnetic resonance imaging (MRI) as well as US have been shown to be more sensitive than clinical examination in detecting enthesitis. However, the clinical significance of these observations is currently unclear, as it may be difficult to identify areas to be scanned and imaging techniques may be expensive and time consuming (86).…”
Section: Radiological Assessment Of Enthesitismentioning
confidence: 99%
“…Correlation of imaging with clinically appreciable tenderness or swelling is limited in enthesitis, which may have implications for validation of clinical measures (85). Studies have shown that ultrasound (US) indices for enthesitis such as the Madrid Sonographic Enthesitis Index (MASEI) can differentiate between patients with…”
Section: Radiological Assessment Of Enthesitismentioning
confidence: 99%